Prophylactic irradiation of para-aortic lymph nodes for patients with locally advanced cervical cancers with and without high CA9 expression (KROG 07-01): A randomized, open-label, multicenter, phase 2 trial. Issue 3 (September 2016) - Kim, Jin Hee; Kim, Joo-Young; Yoon, Mee Sun; Kim, Young Seok; Lee, Jong Hoon; Kim, Hak Jae; Kim, Hunjung; Kim, Yeon-Joo; Yoo, Chong Woo; Nam, Byung-Ho; Kim, Tae Hyun; Kim, Suk-Ki; et al.
Abstract: Background and purpose: The efficacy of prophylactic extended-field irradiation (EFI) plus concomitant cisplatin in patients with locally advanced uterine cervical cancer (LAUCC) is unknown, nor is it known whether tumor carbonic anhydrase IX (CA9) expression level, a hypoxia marker, influences survival outcome. Material and methods: We recruited patients with UCC, FIGO stage IB1 with pelvic lymph node (LN) metastases to IVA with negative para-aortic LN on PET/CT. CA9 expression was examined and patients were randomized to either EFI or pelvic only radiotherapy (PRT) in each CA9 group. The primary outcomes were para-aortic recurrence-free survival (PARFS) and disease-free survival (DFS). Results: Between 2006 and 2011, 79 patients with CA9-positive and 37 with CA9-negative tumors were enrolled, respectively. The median follow-up period was 69.2 months (range 6.8–102.1). For CA9-positive patients, 5-year PARFS was 100% and 81.7% for those receiving EFI and PRT ( p  = 0.007), respectively. DFS was 78.6% for EFI and 71.3% for PRT patients ( p  = 0.353). For CA9-negative patients, 5y PARFS was 100% and 94.1% for EFI and PRT ( p  = 0.317), respectively. DFS was 100% for EFI and 70.7% for PRT ( p  = 0.018). Conclusion: EFI significantly reduced recurrences in PAN in patients with CA9-positive tumors, but survival outcome was not improved, due to high local recurrence and high distant metastases rates. This study indicates the necessity for new therapeutic strategies for LAUCC patients whose tumors show high CA9 expression.